Sensitivity and tunability of heptamer clusters composed of asymmetric split nanorings. (10th June 2015) - Zhang, Wanwan; Feng, Yuanming; Zhang, Yanxiao; Chen, Wanli; Lin, Wang
Abstract: We investigate the multiple Fano resonances in plasmonic heptamer clusters comprising of asymmetric nanorings (H-ANR) with angular split gaps by FDTD simulations. Evolution of the extinction spectra is demonstrated for various angular gaps. By modifying the angular gaps, we show large tunability of the Fano resonances on both the frequency position and the modulation depth. Sensing properties of the H-ANR are studied by the shift of Fano resonances in different dielectric environments or with different thicknesses of p -mercaptoaniline ( p MA) thin films. As for the robustness of the H-ANR, the Fano resonances may be affected by the displacement of the center nanoring, depending on the displacement direction. Our study shows that the H-ANR structure has high tunability and is a good candidate for optical sensing.